IMF Staff papers, Volume 37 No. 2. (IMF Staff Papers; IMF Staff Papers ;, 1990)
This paper examines the macroeconomic effects of IMF-supported adjustment programs. The evidence is reviewed for such effects, and new estimates are provided of these effects for 69 developing countries with programs during 1973-88. The empirical analysis indicates that in the short term, programs have led to an improvement in the current account and the balance of payments, a lowering of inflation, and a decline in growth. In the longer term, the positive effects of programs on the external balance and inflation are strengthened, and the adverse growth effects reduced.